Targeting tumor-infiltrating tregs for improved antitumor responses - Qin, Diyuan; Zhang, Yugu; Shu, Pei; Lei, Yanna; Li, Xiaoyu; Wang, Yongsheng (Frontiers in Immunology, 2024)
Immunotherapies have revolutionized the landscape of cancer treatment. Regulatory T cells (Tregs), as crucial components of the tumor immune environment, has great therapeutic potential. However, nonspecific inhibition of Tregs in therapies may not lead to enhanced antitumor responses, but could also trigger autoimmune reactions in patients, resulting in intolerable treatment side effects. Hence, the precision targeting and inhibition of tumor-infiltrating Tregs is of paramount importance. In this overview, we summarize the characteristics and subpopulations of Tregs within tumor microenvironment and their inhibitory mechanisms in antitumor responses. Furthermore, we discuss the current major strategies targeting regulatory T cells, weighing their advantages and limitations, and summarize representative clinical trials targeting Tregs in cancer treatment. We believe that developing therapies that specifically target and suppress tumor-infiltrating Tregs holds great promise for advancing immune-based therapies.